Section Cesarean in Urban Areas Indonesia: How the Relation with Frequencies of Antenatal Care? - Pristya, T Y R; Fithriyatul Mas’udah, A (KnE Life Sciences, 2019)
Increasing cesarean delivery in Indonesia from year to year has risks to the health of mother and baby. Antenatal care routinely that is suitable with pregnancy trimester is necessary to determine the condition and evaluation of infant health. This research aimed to know the relationship between the frequency of antenatal care with section cesarean. This research is quantitative research with a cross-sectional design. Data were from women aged 15-49 questionnaires of the 2012 Indonesia Demographic and Health Survey (IDHS 2012). The sample used the sample of 5143 women age 15-49 who gave birth to the last child with cesarean delivery or not in urban areas selected in the sample IDHS 2012. Multivariate logistic regression analysis was used to study the related frequency of antenatal care with section cesarean, adjusting for socioeconomic status and education. The rate section cesarean in this research was 23.0% among all women, 14.0% with 0-3 frequencies and 23.4% with >=4 frequencies of antenatal cares. After adjusting for socioeconomic status and mother’s education variable, it showed a statistically significant association between frequencies of antenatal care and section cesarean (p-value 0.046). The result also showed that frequencies of antenatal care >=4 times has 1.7 times higher (95% CI 1.1-2.8) to section cesarean compared with women who 0-3 times of antenatal care. Keywords: section cesarean, frequency, antenatal care